2012
DOI: 10.1002/app.36696
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amine‐terminated butadiene‐acrylonitrile/clay combinations on the structure and properties of epoxy nanocomposites

Abstract: The effect of the clay content and the method of its combination with amine-terminated butadiene-acrylonitrile (ATBN) on the structure and behavior of epoxy was studied. In the case of the simultaneous addition of both components, the increasing clay content had a very small effect on the size of the reaction-induced phase separationformed particles at 5% rubber content due to predominant elimination of two major clay effects, i.e., the nucleation due to phase separation and the kinetics. As a result, both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…These effects include clay nucleation [25], which leads to an earlier onset of phase separation [36] at lower conversion and viscosity, as well as a longer interval between the onset of phase separation and gelation [11]. These results represent a difference from epoxy/liquid rubber/clay systems [11,12], in which an increase in particle size was found. This difference can be explained by the expected lower significance of the pinning effect of clay on the phase separation of the modifier as a result of the significantly lower molecular weight (i.e., in the system with the less significant asymmetry).…”
Section: Effect Of Clay On Structurementioning
confidence: 96%
See 3 more Smart Citations
“…These effects include clay nucleation [25], which leads to an earlier onset of phase separation [36] at lower conversion and viscosity, as well as a longer interval between the onset of phase separation and gelation [11]. These results represent a difference from epoxy/liquid rubber/clay systems [11,12], in which an increase in particle size was found. This difference can be explained by the expected lower significance of the pinning effect of clay on the phase separation of the modifier as a result of the significantly lower molecular weight (i.e., in the system with the less significant asymmetry).…”
Section: Effect Of Clay On Structurementioning
confidence: 96%
“…The primary shortcoming is the increase in viscosity that limits the content of the modifier. An increasing number of studies have indicated not only that nanofillers (NF) can compensate for the stiffness reduction of impact-modified polymeric systems but also that a suitable combination of NF and a polymeric modifier can also provide a synergistic effect (e.g., further increasing the material toughness) [7][8][9][10][11][12][13][14][15][16]. The enhanced efficiency of impact modifiers allows their content to be reduced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, suitable modifications can enhance HNT efficiency [17,18]. However, the evaluation of the structure-directing potential of HNT in polymer [19][20][21][22][23] is in its infancy stage, especially in comparison with that of oMMT [24][25][26][27]. Although the application of PLA and other high performance polyesters in the form of short reinforcing fibres [28,29] in polymer-polymer composites could be a radical alternative to the use PCL/ PLA blends, a significant limitation of this method is the difficult dispersion of compliant fibres in the polymer matrix and their relatively poor adhesion to it [30].…”
Section: Introductionmentioning
confidence: 99%